Sadivayal Village Development Model - Sreeni K R (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2020)
Under the concept of Amrita Self Reliant Village (Amrita SeRVe) has adopted Sadivayal village, Coimbatore, one of the remote tribal villages of Tamilnadu, to develop it as first Smart Village. The village is situated 45 km away from Coimbatore District, having 46 families with an average population of 150 belongs to the Irula Community of Scheduled Tribes. Amrita SeRVe smart village focuses on how villagers utilize local resources in better ways, access to food and nutrition, education, healthcare, access to clean water and sanitation. In Amrita, SeRVe agriculture acts as a catalyst for development and capable of addressing unemployment, health, education, gender equality, and boost income. Sadivayal became our first organic agriculture certified village in Coimbatore District, Tamil Nadu,which applies the standards set by the National Programme for Organic Production (NPOP). In 2018 the village beame open defecation free (ODF). The paper highlights some of the notable Model Village efforts of India and what have been their development indicators i n the backdrop of Sustainable Development Goals (SDG’s) . Also, what Amrita SeRVe acheived compared to model Village initiative of Central Government: the Sansad Adarsh Gram Yojana .